Pengawasan Partisipatif Bawaslu Kendal Terhadap Pilkada di Kabupaten Kendal Tahun 2020 Perspektif Maqashid Syariah - Novi Cahyaningsih; Dahrul Muftadin (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Participatory supervision is an initiative activity outside the supervisory agency to ensure the stages of the general election run by collecting data, information, and making an inventory of the results of cases relating to the holding of general elections and/or regional head elections conducted by independent and non-governmental groups or community organizations. partisan. This concept seems to contain efforts to realize the value of community sovereignty. Where this process becomes the basic foundation of democratic practice. The concept of Islamic law has offered such protection efforts which are then packaged in the concept of Fiqh Siyasah. This continues to be developed in the maqashid syariah theory. The value of benefit is the point of study of MaqÄá¹£id ash-SyarÄ«Ê»ah. Benefits and/or sovereignty need to be implemented in the practice of holding simultaneous regional head elections in 2020. Basically, the practice of holding regional head elections is the implementation of maintaining community sovereignty. This research is a qualitative research with a sociological juridical approach to be further presented as analytical descriptive data. This research took place at the Bawaslu of Kendal Regency. This study aims to determine the practice of participatory supervision of simultaneous regional head elections in 2020 and the practice of analyzing maqashid syariah as a theory of implementing the value of the benefit of participatory supervision carried out in the election of regents and deputy regents of Kendal district for the 2020-2024 period.